FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BERHENTI MEROKOK PADA SISWA PEROKOK SMP X DI KOTA SEMARANG - Yashinta Graycilia Winoto; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2018)
WHO estimates the mortality rate from cigarettes by 2020 will increase by 10 million annually. The number of teenage smokers in 2016 is targeted to fall from 7% to 5.2% but increase to 8.8%. The purpose of this study to determine the factors that can affect the intention to stop smoking in adolescents, especially in junior high school students. This research is a quantitative research with cross sectional approach. Samples were selected using total population obtained through questionnaire with inclusion criteria were male students with active smokers in SMP X Semarang, amounting to 76 students. The data were collected through interviews using questionnaires. Data analysis was done univariat and bivariate with Chi-Square test. The majority of respondents included in the early teenage category of 14 years old (59.2%), age of smoking at age 12 years (40.8%) had pocket money above the average of Rp 11,500 (85.5%), and attended class VIII (69.7%). Most respondents had supporting knowledge (61.8%), supportive attitude to quit smoking (57.9%), supporting parenting role to quit smoking (36.9%), supporting supportive roles for stopping smoking (60.5%), supporting teacher's role to quit smoking (59.2%), having inhibiting factors (65.7%), and supporting factors (51.3%). The variables related to the intention to stop smoking are: respondent's knowledge (p-value 0,001), respondent attitude (p-value 0,004), teacher's role (p-value 0,004) and supporting factor (p-value 0,021). The variables that are not related to the intention to stop smoking are: the role of the respondent's parents (p-value 0.281), the role of the respondent's friend (p-value 0.241) and the inhibiting factor (p-value 0.117)